2022
DOI: 10.3390/met12050828
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Properties of FeSiBCr Amorphous Soft Magnetic Composites by Annealing Treatments

Abstract: Fe-based amorphous powder cores (AMPCs) were prepared from FeSiBCr amorphous powders with phosphate–resin hybrid coating. The high-frequency magnetic properties of AMPCs annealed at different temperatures were systematically studied. After annealing at low temperatures, the effective permeability and core loss improved due to the internal stress of the powder cores being released. The sample annealed at 480 °C exhibits the lowest hysteresis loss of about 29.6 mW/cm3 at 800 kHz as well as a maximum effective pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…They also found that the content of La has an important effect on the primary crystallization temperature and the secondary crystallization temperature of the alloys. Yu et al [4] prepared Fe-based amorphous magnetic cores (AMPCs) from FeSiBCr amorphous powders with phosphate-resin hybrid coatings. The high-frequency magnetic properties of AMPCs annealed at different temperatures were systematically studied.…”
Section: Contributionsmentioning
confidence: 99%
“…They also found that the content of La has an important effect on the primary crystallization temperature and the secondary crystallization temperature of the alloys. Yu et al [4] prepared Fe-based amorphous magnetic cores (AMPCs) from FeSiBCr amorphous powders with phosphate-resin hybrid coatings. The high-frequency magnetic properties of AMPCs annealed at different temperatures were systematically studied.…”
Section: Contributionsmentioning
confidence: 99%
“…Furthermore, the ideal annealing temperature is typically 80-120 • C lower than T x1 , serving as a guideline for annealing [20]. Figure 2c shows two crystallization peaks, with the first corresponding to the α-Fe phase precipitation and the second to the Fe-B phase formation [21][22][23][24]. The crystallization peak temperatures of CAF4 are lower than those of 1K101, with a difference (∆T p ) of 113 • C. Based on DSC results and the XRD pattern of the amorphous iron core, shown in Figure 2c, it is evident that when CAF4 is annealed at ≤290 • C, it remains in an amorphous state, as indicated by a diffuse diffraction peak near 2θ = 45 • .…”
Section: Structure and Performance Analysis Of The Caf4 Stripmentioning
confidence: 99%
“…Furthermore, the ideal annealing temperature is typically 80-120 • C lower than T x1 , serving as a guideline for annealing[20]. Figure2cshows two crystallization peaks, with the first corresponding to the α-Fe phase precipitation and the second to the Fe-B phase formation[21][22][23][24]. The crystallization peak temperatures of CAF4 are lower than those of 1K101, with a difference (∆T p ) of 113 • C.…”
mentioning
confidence: 99%
“…Metastable Fe 3 B is an attractive magnetic compound due to its large saturation magnetization and reasonably strong magnetic anisotropy. In particular, it appears in various important magnetic materials, such as nanocomposite permanent magnets (e.g., Fe 3 B/Nd 2 Fe 14 B) [ 2 , 3 , 4 , 5 ] and Fe-B-based amorphous and nanocrystalline soft magnetic alloys [ 6 , 7 , 8 , 9 ]. For the nanocomposite permanent magnets, Fe 3 B, as the main phase and providing large saturation magnetization, interacts with hard magnetic phase (e.g., Nd 2 Fe 14 B) by exchange-coupling interaction, achieving large energy production.…”
Section: Introductionmentioning
confidence: 99%